Mao's last dancer - Li, Cunxin 1961- (Putnam, 2003)
In a memoir of life in Maoist China, the author describes how he was taken from his family in rural China to study ballet in Beijing, his rise in the world of Chinese ballet, and his defection at age eighteen to the United States.
Keywords: Li, Cunxin <1961->; Li, Cunxin -- 1961-; Geschichte 1972-1979; Ballet dancers -- China -- Biography; Defectors -- China -- Biography; Erfolg; Junge; Tanz; Tänzer; Ballett; China; Autobiografie